2020
DOI: 10.1038/s41598-020-70413-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral tissue pO2 response to treadmill exercise in awake mice

Abstract: We exploited two-photon microscopy and Doppler optical coherence tomography to examine the cerebral blood flow and tissue pO 2 response to forced treadmill exercise in awake mice. to our knowledge, this is the first study performing both direct measure of brain tissue pO 2 during acute forced exercise and underlying microvascular response at capillary and non-capillary levels. We observed that cerebral perfusion and oxygenation are enhanced during running at 5 m/min compared to rest. At faster running speeds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Based on studies in awake rats under hypoxic breathing conditions (Dunn et al, 2011;Ortiz-Prado et al, 2010), there is a similar percentage drop between arterial and tissue pO 2 that lasts for exposures of 1-2 days. The theoretical prediction of tissue pO 2 being maintained during activation within 10% boundaries during activation is in agreement with recent measurements in activated brain regions in awake mice (Moeini et al, 2019(Moeini et al, , 2020Zhang et al, 2019), and previous fitting of experimental CBF versus CMRO 2 data (Buxton, 2010;Buxton et al, 2014;Herculano-Houzel & Rothman, 2022;Ji et al, 2021).…”
Section: Effect Of Changes In Blood and Tissue Ph Pco 2 And Po 2 On ...supporting
confidence: 90%
See 1 more Smart Citation
“…Based on studies in awake rats under hypoxic breathing conditions (Dunn et al, 2011;Ortiz-Prado et al, 2010), there is a similar percentage drop between arterial and tissue pO 2 that lasts for exposures of 1-2 days. The theoretical prediction of tissue pO 2 being maintained during activation within 10% boundaries during activation is in agreement with recent measurements in activated brain regions in awake mice (Moeini et al, 2019(Moeini et al, , 2020Zhang et al, 2019), and previous fitting of experimental CBF versus CMRO 2 data (Buxton, 2010;Buxton et al, 2014;Herculano-Houzel & Rothman, 2022;Ji et al, 2021).…”
Section: Effect Of Changes In Blood and Tissue Ph Pco 2 And Po 2 On ...supporting
confidence: 90%
“…Another limitation of this study is that the calculations of average tissue pCO2 and pnormalO2, do not provide information on their microscopic blood and tissue distribution within a neurovascular unit. Based upon recent studies using high resolution optical imaging, regional pnormalO2T levels within a neurovascular unit vary between approximately 2.0–0.5 times the mean value (Gould et al, 2017; Li et al, 2019; Lyons et al, 2016; Mächler et al, 2022; Moeini et al, 2018, 2019, 2020), The lower end of this range may explain the sensitivity of brain function to decreases in pnormalO2T being greater than anticipated from average values. Due to its 20‐fold higher diffusivity, the range of pCO2T is anticipated to be similar to the difference in arteriole and venule values (see Equation 34).…”
Section: Discussionmentioning
confidence: 99%
“…could be in part due to an increase in Hct level due to exercise. (Moeini et al, 2020) We observed a moderate but statistically insignificant increase in Hct in the exercise group compared with sedentary mice (Figure 4c). No difference in the capillary RBC line-density between two groups was found (Figure 3 -Figure supplement 2).…”
Section: Aging-induced Reduced Microvascular Oxygenation In Deeper Co...mentioning
confidence: 76%
“…The idea that components of enrichment, such as exercise, can augment cerebral blood flow and therefore could affect capillary recanalization, is not new. Many rodent studies have shown that exercise can increase capillary blood flow, tissue oxygenation, and microvascular density in the cerebral cortex (Swain et al, 2003;Murugesan et al, 2012;Huang et al, 2013;Moeini et al, 2020). Indirect evidence that exercise might improve recanalization comes from the fact that it could prevent the inevitable consequence of recanalization failure (Reeson et al, 2018), namely, vessel pruning and the appearance of string vessels (Leardini-Tristão et al, 2020;Trigiani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%